2017
DOI: 10.1103/physrevlett.119.043604
|View full text |Cite
|
Sign up to set email alerts
|

Collective Optomechanical Effects in Cavity Quantum Electrodynamics

Abstract: We investigate a cavity quantum electrodynamic effect, where the alignment of two-dimensional freely rotating optical dipoles is driven by their collective coupling to the cavity field. By exploiting the formal equivalence of a set of rotating dipoles with a polymer we calculate the partition function of the coupled light-matter system and demonstrate it exhibits a second order phase transition between a bunched state of isotropic orientations and a stretched one with all the dipoles aligned. Such a transition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…(1) because the two-level systems are saturable. However, such effects were shown in [44] to not significantly change the behavior. (We also consider this further below.)…”
Section: Model and Summary Of Previous Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…(1) because the two-level systems are saturable. However, such effects were shown in [44] to not significantly change the behavior. (We also consider this further below.)…”
Section: Model and Summary Of Previous Resultsmentioning
confidence: 94%
“…The solution of this equation increases from x 0 = 0 at a = 0 to reach x 0 = 1 when a = 8. By definition, |x 0 | < 1, and so this Gaussian polymer approximation predicts that at a = 8, a second order transition occurs to a fully ordered state [44].…”
Section: Model and Summary Of Previous Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of this effect depend on the precise setup, such as the cavity material and shape, molecular and solvent properties, etc., and would require a more complete treatment taking thermodynamical effects and free energy into account [111,112], which is beyond the scope of the current work. However, we mention that it has recently been shown that strong coupling and the associated formation of polaritons itself could lead to alignment due to the associated decrease of the lower polariton energy, provided that a significant fraction of molecules are excited to lower polariton states [29,113]. Although thermal excitation can be efficient for vibrational strong coupling due to the relatively low energies of vibro-polaritons, on the order of a few times the thermal energy k B T , it should be noted that the arguments in [29,113] do not directly translate to thermal-equilibrium situations.…”
Section: Collective Effectsmentioning
confidence: 99%
“…Many works demonstrated how the hybridization with matter strongly alters not only the spectrum, but also the field profile [2][3][4], and the quantum [5][6][7][8] and nonlinear [9,10] properties of the photonic resonator. More recently interest has also broadened to investigate how strong coupling can be used to modify properties of the underlying matter degrees of freedom [11][12][13][14][15][16][17][18], including changes in electrical [19][20][21][22][23] and photochemical [24][25][26][27] properties.…”
Section: Introductionmentioning
confidence: 99%